PENGARUH WORKING CAPITAL TURNOVER, DEBT TO TOTAL ASSET DAN RECEIVABLE TURNOVER TERHADAP PERTUMBUHAN LABA - Surya Ridhoansyah; Zenni Riana; Eli Agustami (Universitas Islam Islam Sumatera Utara, 2021)
This study aims to determine the effect of working capital turnover, debt to total assets and receivable turnover with profit growth. The type of data used is quantitative data. Determination of the sample was carried out using purposive sampling technique, and there were 12 companies in the food and beverage sector that were sampled in this study. The data analysis technique used is multiple linear regression analysis. The data source used is secondary data obtained from the Indonesia Stock Exchange, by taking financial statement data, in 2017 to 2020. The results of this study indicate that partially debt to total assets has a positive and significant effect on profit growth, and receivable turnover has an effect negative and significant to profit growth. Meanwhile, working capital turnover has no and no significant effect on profit growth.